ARGUMEN DALAM KARYA ILMIAH DOSEN PADA JURNAL TERAKREDITASI AL-TAHRIR STAIN PONOROGO BERDASARKAN TEORI PENALARAN MODEL TOULMIN - Sova Puspidalia, Yuentie (Widya Warta, 2015)
This research  focuses its analysis on the patterns and elements of arguments used by the authors in the journal Al-tahrir of STAIN Ponorogo. The method used is descriptive - qualitative in nature. The results revealed two patterns of reasoning, namely deduction and induction. In this case, induction was over deduction due to their frequency of use.  The analysis also found  some errors in the reasoning as a result of mistakes in relation or relevance and analogy. The elements of the arguments used in connection with Toulmin model were claim, ground, warrant, backing, modal qualifier, and rebuttal.  Among them, claim and ground elements were most widely used. The authors of the articles could implement the reasoning of Toulmin model because this kind of reasoning has some advantages when compared to traditional reasoning.